The soil and its relationship with ecosystem services and food security - Burbano-Orjuela, Hernán (Revista de Ciencias Agrícolas, 2016)
This text discusses the importance of soil as a natural resource. It highlights the benefits derived from soil for both ecosystem and society, as a provider of ecosystem services and as a major player in guaranteeing food security.